New species of Galathea Fabricius, 1793 and Nanogalathea Tirmizi & Javed, 1980 (Crustacea: Decapoda, Galatheidae) from the Western Pacific - Macpherson, Enrique; Rodríguez-Flores, Paula C.; Machordom, Annie (Zootaxa, 2025)
Specimens of squat lobsters belonging to the family Galatheidae, representing the genera Galathea and Nanogalathea, were collected during several cruises carried out in New Caledonia, Papua New Guinea, the Philippines and Phoenix Islands. The study of these specimens integrating molecular and morphological data revealed the presence of eight new species in Galathea and one in Nanogalathea. We describe and illustrate these new species. Molecular data from mitochondrial markers were also included to support the taxonomic status of the species. Finally, a key to species for the genus Galathea from the Indian and Pacific Oceans is also provided.